Indonesia's support in the ongoing conflict between Israel and Palestine - Afri Emilia Br Sembiring; Kemala Oktreza (CV. Rayyan Dwi Bharata, 2024)
Palestine is a country in the Middle East whose political status is still under debate. Some countries in the world, including ASEAN, have recognized the existence of the state of Palestine, but there are still several countries in the world, including the United States, that have not recognized the existence of the state of Palestine. This then also became one of the reasons for the prolonged conflict between Israel and Palestine. This conflict has been going on for hundreds of years, from the end of the 19th century to the current 21st century. October 2023 is the beginning of the Israeli and Palestinian conflict once again becoming a very serious topic of discussion in the international world towards the end of 2023. As a country that has had relations with the Middle East, including Palestine, since before independence, Indonesia has a role in the peaceful solution that is expected to occur in Israel and Palestine. This paper aims to look at the support of Indonesia in responding to the prolonged Israeli-Palestinian conflict. Why doesn't this conflict end? Does this conflict have the potential to end? This paper is used descriptive study method and analysis by the authors.